Pengaruh Literasi Keuangan Dan Toleransi Risiko Terhadap Keputusan Investasi (Studi Pada Warga Desa Sekapuk Kabupaten Gresik) - Rizkyatul Nadhifah; Muhadjir Anwar (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of financial literacy and risk tolerance owned by Sekapuk Village residents of Gresik Regency as investors. The population in this research is the residents of Sekapuk Village, Gresik Regency who become investors in 2020. The sample is 80 respondents with random sampling technique. Data was collected by distributing questionnaires which were then analyzed using SEM with the PLS application. The results of this study indicate that financial literacy has a positive and significant impact on investment decisions for the residents of Sekapuk Village, Gresik Regency. Financial literacy has a positive and significant effect on risk tolerance for residents of Sekapuk Village, Gresik Regency. Risk tolerance has no significant effect on investment decisions for the residents of Sekapuk Village, Gresik Regency. Risk tolerance disable to act as a mediating variable.